2015
DOI: 10.3109/10717544.2015.1041580
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of doxorubicin and vincristine to lymph cancer: evaluation of novel nanostructured lipid carriers in vitro and in vivo

Abstract: Purpose: Lymph cancers are heterogeneous malignancies of the hematopoietic and lymphoid tissues. Doxorubicin (DOX) and vincristine (VCR) are commonly used anti-cancer chemotherapeutic drugs, but their clinical uses are associated with dose-limiting systemic toxicity. Methods: In the present study, DOX and VCR were encapsulated into nanostructured lipid carriers (NLCs) and used them to treat B-cell lymphoma cells through the targeted delivery of DOX and VCR to lymph cancer animal model. Results: DOX and VCR enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…The high loading capacity of NLCs formulation has offered multiple solutions to such problem, as it was possible to collectively incorporate a combination of chemotherapeutic agents in the same NLC particle. This approach can be used not only to control the release of both drugs, but also to enhance their anticancer effect through their integrated influence [91]. For example, Dong et al prepared NLCs containing a combination of doxorubicin (DOX) and vincristine (VCR) to overcome drug resistance after chemotherapy and the potential for relapses in lymph cancer.…”
Section: Applications Of Nlcs In Delivery Of Chemotherapeutic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high loading capacity of NLCs formulation has offered multiple solutions to such problem, as it was possible to collectively incorporate a combination of chemotherapeutic agents in the same NLC particle. This approach can be used not only to control the release of both drugs, but also to enhance their anticancer effect through their integrated influence [91]. For example, Dong et al prepared NLCs containing a combination of doxorubicin (DOX) and vincristine (VCR) to overcome drug resistance after chemotherapy and the potential for relapses in lymph cancer.…”
Section: Applications Of Nlcs In Delivery Of Chemotherapeutic Agentsmentioning
confidence: 99%
“…This prolonged release was accompanied by a sustained antitumor effect during tumor progression. DOX-NLC, VCR-NLC, DOX-VCR-NLC, and drug solution were compared in lymph cancer animal model and the results showed that DOX-VCR-NLC exhibited more controlled release with synergistic effects and potent anti-tumor activity which was demonstrated by the inhibition of B-cell lymphoma [91].…”
Section: Applications Of Nlcs In Delivery Of Chemotherapeutic Agentsmentioning
confidence: 99%
“…In the study, based on some previous reports by other researchers, 36 we designed and carried out pre experimental research. We set the ratios of VCR/DOX (1:1, 3:1, 5:1) to study the inhibitory effect of A549 cell under different ratios.…”
Section: Preparation Of Npsmentioning
confidence: 99%
“…Moreover, the utilisation of cyclophosphamide and vincristine potentially inhibit the metastases during two months of the observed periods. Cyclophosphamide is the alkylating agent that able to bind the DNA and depress the DNA replication and mitosis (Prajapati et al, 2017), and vincristine binds the tubulin to inhibit cell's metaphase (Dong et al, 2016).…”
Section: Resultsmentioning
confidence: 99%